ANALYSIS OF STUDENTS' RESPONSES TO BIOLOGY TEACHING MATERIALS BASED ON AL QUR’AN VALUES - Eriawati, Eriawati; Hanim, Nafisah (Universitas Islam Negeri Ar-Raniry, 2023)
Teaching materials are one of the important components in the learning process. Teaching materials must be in accordance with basic competencies in order to achieve learning objectives. This study aims to analyze the response of students at the MA / SMA level in Aceh Province to biology teaching materials based on Koranic values. this research uses an R&D design. teaching materials that will be given to students have passed the development phase and expert validation. The instrument used was a learner response questionnaire which was tested twice, on a small scale and large scale. Data analysis using the percentage response formula. The results showed that the response of MA / SMA level students in Lhoksumawe City, Pidie and Aceh Besar Aceh Province was very interested in biology teaching materials based on Quranic values. the results of the analysis obtained from the calculation of a small scale (30 students) obtained a response with an average value of 89.93 and a large scale (70 students) with an average value of 90.79.